Learning by Gaming: Extramural English Gaming Effect on Indonesian Senior High Students’ Pragmatic Competence - Dirwan, Muh Ilham; Surtini, Ni Wayan; Muhammad Zulfadhli (Journal of Pragmatics Research, 2025)
Several studies have found that learning English outside of school through Extramural English (EE) activities such as online gaming can enhance students’ English language ability. However, not many information exists on whether this so-called extramural English gaming activity has implications on students’ pragmatic competence. To answer that, this study aims to explore the effect of extramural gaming activity toward students’ pragmatic competence. The research was done by employing a task called the Multiple-Choice Discourse Completion Task (MCDCT) on 60 second-grade students interested in extramural gaming activity (male = 26, female = 34) in Luwuk, Indonesia. Students were divided into two groups, 30 gamer students and 30 non-gamer students. The students were instructed to answer several real-world communicative situations given in the MCDCT task. The data analyzed using statistical descriptive methods. The results of the study revealed that students who frequently played online games (M=3.523) were slightly better at doing the MCDCT than non-gamer students (M=3.220). Thus, it concluded that extramural gaming activity positively affected students’ pragmatic competence.